RESISTENSI PEREMPUAN TERHADAP TRADISI KAWIN TANGKAP MASYARAKAT ADAT SUMBA (Analisis Narasi William Labov dalam Buku Perempuan yang Menangis kepada Bulan Hitam Karya Dian Purnomo) - Alya Purnomo, Fahrina; Sunarto, Sunarto; Dwiningtyas Sulistyani, Hapsari (Interaksi Online, 2024)
Women are the gender group that dominates the number of migrant workers in Indonesia. The Captive marriage is still a long-standing tradition practiced by the Sumba community in East Nusa Tenggara, even today. Capture marriage is a form of forced marriage through forms of violence, including physical, social, psychological and sexual. In order for the proposal in a capture marriage to be accepted immediately, the perpetrator even forces the victim by inciting or the worst is by raping the victim. this research uses Helen Cixous's feminine ecriture theory. The method used in this research is William Labov's narrative analysis, which will be used to analyze the novel entitled Perempuan yang Menangis kepada Bulan Hitam by Dian Purnomo, through six narrative structures, namely abstract, orientation, complication, evaluation, resolution, and coda, so that it can be known the forms of women's resistance to the tradition of capture marriage in the book Perempuan yang Menangis kepada Bulan Hitam. Through the character of Magi Diela, the author tries to represent the values of women's resistance to the capture marriage tradition. Women's resistance in the novel Perempuan yang Menangis kepada Bulan Hitam is shown in Chapter 1, Chapter 7, Chapter 8, Chapter 9, Chapter 10, Chapter 12, Chapter 13, Chapter 20, Chapter 21, Chapter 25, Chapter 34, Chapter 52, Chapter 55, and Chapter 56. The resistance carried out can take the form of open resistance and closed resistance. The open form of resistance carried out by the main character is suicide because she refuses to be married to the perpetrator of the arranged marriage, struggling and kicking the kidnapper, shouting at the perpetrator of the arranged marriage as a 'rapist', hunger strike, fleeing from Sumba to Kupang, becoming a bait to imprison the perpetrator, and reporting the perpetrator of the arranged marriage to the police. Meanwhile, the closed form of resistance carried out by the main character is writing about the rights of women victims of capture marriage and the main character's experience as a victim of capture marriage, swearing, cursing, cursing in the heart, and the main character who promises to take revenge on the people involved in capture marriage.